2022
DOI: 10.1136/bjsports-2021-104851
|View full text |Cite
|
Sign up to set email alerts
|

Determining Sport Concussion Assessment Tool fifth Edition (SCAT5) reliable change in male professional hockey players

Abstract: ObjectivesThe purpose of this paper is to provide reliable change metrics and assess the test–retest psychometrics of the Sport Concussion Assessment Tool fifth Edition (SCAT5) in a multilingual sample of professional ice hockey players.MethodsThe SCAT5 was administered to National Hockey League and American Hockey League male professional ice hockey players as part of the 2018 and 2019 season medical evaluations. We extracted data from an existing clinical database of players who were administered two consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Five studies published test–retest reliability for SCAT5 subtests. Test–retest reliability for component and total SAC scores was poor, ranging between 0.22 and 0.52 61 62 71–73. Base rates enable the quantitative interpretation of multiple tests simultaneously, reducing the risk of false-positive results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies published test–retest reliability for SCAT5 subtests. Test–retest reliability for component and total SAC scores was poor, ranging between 0.22 and 0.52 61 62 71–73. Base rates enable the quantitative interpretation of multiple tests simultaneously, reducing the risk of false-positive results.…”
Section: Resultsmentioning
confidence: 99%
“…Base rates enable the quantitative interpretation of multiple tests simultaneously, reducing the risk of false-positive results. One study examined base rates of decline on the SCAT5 using reliable change indices 71. Findings showed that decline at the 0.80 CI (32.3% of sample) or 0.90 CI (20.7% of sample) level on only one of three considered SCAT5 subtests was relatively common in a non-concussed sample 71.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…97,[102][103][104] If the symptoms of the soccer player combined with video-analysis suggest a concussion, there are specific diagnostic tools to substantiate the diagnosis: the Standardized Assessment of Concussion can be used directly, 103 the Sport Concussion Assessment Tool (SCAT5) is applied off-field. 105…”
Section: Diagnosismentioning
confidence: 99%